Forest passerines as a novel dispersal vector of viable bryophyte propagules. Issue 1897 (20th February 2019) - Chmielewski, Matthew W.; Eppley, Sarah M.
Abstract : Animal dispersal influences the community structure and diversity of a wide variety of plant taxa, yet the potential effects of animal dispersal in bryophytes (hornworts, liverworts, and mosses) is poorly understood. In many communities, birds use bryophyte-abundant niche space for foraging and gathering nest material, suggesting that birds may play a role in bryophyte dispersal. As highly motile animals with long migratory routes, birds potentially provide a means for both local and long-distance bryophyte dispersal in a manner that differs greatly from passive, aerial spore dispersal. To examine this phenomenon, we collected and germinated bryophyte propagules from the legs, feet and tails of 224 birds from 34 species within a temperate forest community. In total we found 1512 spores, and were able to germinate 242 bryophyte propagules. In addition, we provide evidence that topical (externally-carried) spore load varies by bird species and behaviour. Tail feather spore abundance is highest in bark and foliage gleaning species and is positively correlated with tarsal length. Together, these data suggest that a variety of forest birds exhibit the potential to act as dispersal vectors for bryophyte propagules, including an abundance of spores, and that understanding the effects of animal behaviour on bryophyte dispersal will be key to further understanding this interaction.